Aneurismas intracraneanos. Nuestra experiencia en 53 casos operados en 3 años - Mendiondo, Ignacio; Mendiondo, Eulogio (Revista Argentina de Neurocirugía, 2021)
A clinical surgical review of 53 cases of intracranial aneurysms operated on from January 1997 to December 1999 was performed.Objetives: To analyze the relationship between the Hunt and Hess grading system, Fisher tomographic scale, vasospasm incidence, surgical strategy and technic as relevant factors in patient outcome.Material and Methods: Our 53 patients showed the following distribution :- Hunt and Hess grade 0: one patient; grade I: 17 patients; grade II: 25 patients; grade III: 8 patients; grade IV: none and grade V: 1 patient.- Fisher scale. Grade I: 3 cases; grade II: 28 cases; grade III: 11 cases and grade IV: 11 cases. Clinical and/ or angiographic vasospasm: 17 patients.- Surgical strategy: early surgery in 25 cases.Results: Patients belonging to Hunt and Hess grades 1 and 2 had a 2.7% mortality rate with a very good outcome in 33 cases and good outcome in 8. Grades 3 to 5 had an overall mortality of 50%.Conclusion: A good outcome was observed in patients included in Hunt and Hess grades 1 and 2 as compared to patients in grades 3 to 5. Furthermore, the patients presurgical consciousness level resulted in the single most important prognostic factor.
Keywords: subarachnoid hemorrhage; intracranial aneurysm; surgical strategy